Participatory museum strategies: reflecting and acting in Sociomuseology (Cadernos de Sociomuseologia, 2014)
The objective this article is to analyze the possibility of communication and the search of informations about virtual Museums’ object on-line between researcher and institution. So, the text was developed by three cases like methodology to compare Virtual Museums (VMs) and Actual Museums (AMs) in aspects that link objects’ informations, quality and quantity these informations and quantity of VM’s collection. With that objective, the three cases accost attempts of communication that researches and a teacher of History of Art kept up to work the research themes and class in VMs respectively. That methodology – approached at case study – made three situations whose intention is to check up the VM's potential, which have actual interfaces. Key words: case, museum, cyberspace